Correction: Pan et al. Lignin-Derived Activated Carbon as Electrode Material for High-Performance Supercapacitor. Molecules 2025, 30, 89 - Chenghao Pan; Yongfeng Ji; Suxia Ren; Tingzhou Lei; Lili Dong (Molecules)
Adjustment of Authorship Order [...]